An exploration of psychological contract violation and calling experienced by religious ministers - Orton, Du Toit (Koers, 2020)
Although individuals who experience a vocational calling tend to be less receptive to psychological distress causing burnout, depression and turnover the prevalence of these cases are on the rise among religious ministers. This hitherto unexplained phenomenon is investigated in this study by exploring psychological contract violation experience with religious ministers in South Africa. A total of 11 participants were interviewed using a narrative approach, forming a qualitative study exploring the content of calling, expectations created by calling in reaction to it and the perceived violation of these expectations in the vocational setting. The result indicates that religious ministers do indeed experience psychological contract violation that leads to a host of negative effects. Opsomming:‘n Ondersoek na psigologiese kontrak skending- en roeping ervaring by geestelike leiers. Alhoewel individue wat ‘n roeping ervaar die geneigdheid het om minder vatbaar te wees vir psigologiese stress wat uitbranding, depressie en omkeer-intensie voorafgaan, is daar ‘n toenemend hoër voorkoms hiervan by geestelike leiers. Hierdie onverklaarde fenomeen word in hierdie studie ondersoek deur psigologiese kontrak verbreking ervarings onder geestelike leiers in Suid Afrika te ondersoek. ‘n Totaal van 11 deelnemers is by wyse van narratiewe onderhoude ondervra om ‘n kwalitatiewe studie te doen wat die inhoud van roeping, verwagtinge vanuit die roeping en beleefde skending van hierdie verwagtinge in die loopbaankonteks te ondersoek. Die resultaat dui daarop dat geestelike leiers wel psigologiese kontrak skending ervaar wat negatiewe gevolge inhou. https://doi.org/10.19108/KOERS.85.1.2480